Pengaruh Perkawinan Di Bawah Umur Terhadap Keharmonisan Rumah Tangga Di Bangkalan – Jawa Timur Dalam Prespektif Hukum Positif Di Indonesia - Sumriyah; Mishbahul Munir; Ayu Windayani (Universitas Merdeka Madiun, 2022)
Abstract— In carrying out a marriage as stipulated in the Marriage Law, the age limit for marriage is regulated, which is a minimum age of 19 years. The prospective bride can make a dispensation that is submitted to the Religious Court if the prospective bride still does not meet the requirements for the age limit for marriage. However, the reality found in society is that there are still many practices of underage marriage without going through a dispensation to the Court. This research is an empirical legal research field research, namely research that is directly carried out to the object of research to obtain relevant data related to the implementation of underage marriages which is the material in the preparation and discussion.